2022
DOI: 10.36941/ajis-2022-0084
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Top Management Support on Change Management, Cloud ERP Implementation, and Performance of SMEs

Abstract: Top management support (TMS) is a critical success factor in cloud computing (CC) implementation and firm performance. However, extant empirical research on these relationships has obtained mixed findings due to earlier studies focusing on a one-dimensional TMS construct with diverse measurement items that muddle up different behaviours of top management. TMS is typically a multi-dimensional construct, such as TMS change management (TMSCM), TMS resource provision (TMSR), and TMS vision sharing (TMSV). The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Further, the two-stage (including the disjoint two-stage and embedded two-stage) and extended repeated indicators approaches are proposed for specifying and evaluating HOCs in PLS-SEM ( Sarstedt et al., 2019 ). In this study, the HOCs were specified and evaluated using a disjoint two-stage approach because it allows for an enhanced parameter recovery of paths to be illustrated ( Jayeola et al., 2022c ; Sarstedt et al., 2019 ). Only the LOCs of the HOCs are considered in a disjoint two-stage method, removing HOCs from the path model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the two-stage (including the disjoint two-stage and embedded two-stage) and extended repeated indicators approaches are proposed for specifying and evaluating HOCs in PLS-SEM ( Sarstedt et al., 2019 ). In this study, the HOCs were specified and evaluated using a disjoint two-stage approach because it allows for an enhanced parameter recovery of paths to be illustrated ( Jayeola et al., 2022c ; Sarstedt et al., 2019 ). Only the LOCs of the HOCs are considered in a disjoint two-stage method, removing HOCs from the path model.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the mediation category (partial or full) is yet unidentified. Partial mediation arises when both the direct and mediating effects are significant, whereas full mediation arises when the direct effect is insignificant but the mediating effect is significant ( Cepada-Carrión et al., 2018 ; Jayeola et al., 2022c ; Yusof et al., 2021 ). The indirect (mediating) effect is significant and the direct effect is insignificant, as earlier explained and as indicated in Table 7 Therefore, a full mediation can be established between GFS and FPER through the sequential mediation of CERPI and CA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So the expectation is that, the greater the work of appropriately managing projects, the greater the need for change management and support from the top management. The literature has shown that the top management team can improve the change management process as they make strategic decisions to guide the company toward success through significant changes (Jayeola et al, 2022). In this regard, considering the above discussion, the following hypotheses were formulated: H1.…”
Section: Critical Success Factors For Company Success Bpm and Change ...mentioning
confidence: 99%
“…Various studies have focused on behavioural changes, for instance Kotter's (1995) 8-step change methodology. Jayeola et al (2022) discussed the role of top management in the adoption of enterprise resource planning (ERP) cloud solutions. Da Veiga (2018) introduced the Prosci's ADKAR (Awareness, Desire, Knowledge, Ability and Reinforcement) change management model to investigate culture change regarding security.…”
Section: Introductionmentioning
confidence: 99%